Bowie : stardust, rayguns & moonage daydreams - Horton, Steve (Insight Comics, 2020)
"As one of the most magnetic icons of modern pop culture, David Bowie seduced generations of fans with his music and counterculture persona. While Bowie's legacy as a musician is remarkable and genre-defying, as a visual performer he obliterate stage theatrics with his psychedelic aesthetics, larger-than-life image, and way of hovering on the border of the surreal. Bowie: Stardust, Rayguns & Moonage Daydreams chronicles the rise of David Bowie's career from obscurity to fame, as well as the rise and fall of Ziggy Stardust, Bowie's historic alter ego. Ziggy accompanies Bowie on his rocky ride to the top, but when the Spiders from Mars finally implode and Bowie leaves London for a nomadic life abroad, he must lay the Ziggy persona to rest for good. The end of Ziggy eventually changes not only Bowie but the world itself. Featuring graphic storytelling by New York Times best-selling artist Mike Allred and critically acclaimed writer Steve Horton that is as colorful and diverse as Bowie's many personas, this graphic biography tells the story of one of the most celebrated and beloved musicians like never before."--